Desenvolvimento de uma técnica inovadora de pigmentação de peças anatômicas plastinadas e de uma ferramenta de ensino de anatomia - Silveira, Helson Freitas (2023)
Anatomy is an essential part of science education and has been a mainstay in the curriculum of students and healthcare professionals around the world. The use of cadavers continues to be the main tool for teaching anatomy in practice. However, maintaining anatomical specimens has been a challenge throughout the history of anatomy. The acquisition and conservation of bodies for teaching has made it difficult to maintain cadaver anatomy as a morphology teaching and research method. Plastination emerged as an innovative conservation technique that offers solutions to various anatomical teaching problems. The plastinated specimens are more stable, with superior visual quality, durable, easy to handle and of low toxicity. However, during the technical stages, there is the inconvenience of loss of natural pigments. To solve this problem, there are color replacement techniques, but most of them require manual and artistic skills and/or have low durability and, in addition, can increase the cost of the technique. In this sense, in the present work, an innovative methodology for the pigmentation of plastinated specimens, resistant and compatible with the chemical and physical processes of plastination, through vascular perfusion, was developed and patented. The proposed method presents good tissue penetration, uniformity of pigment distribution, easy application, stability and resistance in plastination process, maintaining the flexibility of the specimens. Additionally, we sought to explore the potential use of pigmented plastinated specimens to produce high-resolution images and the possibility of using them as a teaching tool in practical classes by associating the specimens’ information and the obtained images with a digital tool called AnatomyID. The AnatomyID tool allows, at the same time, to store images and catalog information from the UFC anatomy laboratory collection, facilitating the location, tracking and providing students and teachers with access to the content of the specimen collection during didactic activities as support material for practical teaching. These themes were exposed, in the present work, in the format of 3 articles: (1) “A new method of pigmentation for plastinated anatomical specimens”, submitted and formatted according to the rules of the journal “Anatomical Science Education”; (2) Patent publication BR 102020001102-2 A2 “Method of pigmentation of organic tissues by perfusion for preservation by low cost plastination” deposited at the National Institute of Industrial Property (INPI) and (3) “AnatomyID: an anatomy learning tool through remote access to an anatomical collection ”, formatted according to the guidelines of the journal “Anatomical Science Education”.